The relationship between the level of vitamin D, leptin and FGF23 in girls and young women with polycystic ovary syndrome - Białka-Kosiec, Agnieszka; Orszulak, Dominika; Gawlik, Aneta; Drosdzol–Cop, Agnieszka (Frontiers in Endocrinology, 2022)
Polycystic ovary syndrome is an endocrinopathy that mainly affects adolescent girls and young women of childbearing age. In girls, the presence of clinical and biochemical symptoms of hyperandrogenism should be particularly considered. The role of vitamin D deficiency in insulin resistance, inflammation, dyslipidemia, and obesity, i.e. in diseases associated with PCOS, has been investigated, which may suggest its involvement in the pathophysiology of the syndrome. Leptin has been shown to stimulate the formation of FGF23 in bones. There is a relationship between the incidence of dyslipidemia, adipose tissue mass and the concentration of fibroblast growth factor 23. The main aim of the presented research project is to assess the concentration of vitamin D, calcium, and selected hormones as well as the concentration of adipokines (leptin) in girls diagnosed with polycystic ovary syndrome. Materials and Methods: The study included a population of 85 girls and young women aged 14 to 22 years. The study group included 37 girls who were diagnosed with polycystic ovary syndrome according to the modified Rotterdam’s criteria. The control group consisted of 48 completely healthy girls. In the first stage of the study participants were required to answer background questions. Next, anthropometric measurements were performed. The laboratory tests assessed: leptin, FGF23, FSH, SHGB, total testosterone, DHEA-S, 25-OH-D3, PTH, calcium, androstadiene, AMH, glucose, insulin. Results: The vitamin D level in the group with polycystic ovary syndrome was lower than in the control group, but there was no statistically significant difference. The level of anti-Müllerian hormone was significantly higher in the group of girls diagnosed with PCOS compared to the control group. Statistically significant differences between both groups were also noted in the HOMA-IR value. The concentration of calcium, parathyroid hormone, FGF23 and leptin in the study and control groups showed no statistically significant difference. Conclusions: In the studied group of girls with PCOS, no correlation between the level of vitamin D and selected parameters such as: AMH leptin, HOMA-IR and FGF23 was confirmed. On this basis, it can be assumed that additional vitamin D supplementation would not reduce the symptoms of polycystic ovary syndrome.